Using the Digital Platforms by Journalists of the Middle East and North Africa (MENA) in Promoting Common Human Values - Abed Khalaf Aleessawi, Najm (Dirasat: Human and Social Sciences, 2022)
Digital platforms had been employed during the ideological, economic, and security conflicts in different world areas with different goals. Sometimes they caused big disputes among individuals and societies, and violated the system of values, through bad posts and publishes this article aimed to find out how journalists use digital content in entrenching common human values, using the descriptive approach, and a questionnaire distributed (during January 2021) to simple random sample included (1568) journalists from Arab middle east and North Africa(MENA). The most important results were; the most digital platforms and applications that adopted by Journalists were facebook in high the rank (mean=4.48), Instagram(mean=4.22), and WhatsApp in the middle rank (3.16). With high rank, the journalists worked through digital media to promote the values of love(mean=4.58) and peace and to promote the spirit of brotherhood in one society(mean=4.57). They used most of the mechanisms of social media to promote highly the values of love and peace; Participation in dialogues and comments on social networks (mean=4.45), and Share publications that call for love and peace(mean=4.36), but it had been displayed that journalists use rarely the films and documentaries(mean=1.65).